PENGARUH VARIASI CAMPURAN EKSTRAK Imperata cylindrica L. dan Ageratum conyzoides L.TERHADAP GULMA DAN PERTUMBUHAN Alium fistulosum L. - Novia Cahyati; Agus Sutanto; Hening Widowati (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
Shallots have a high economic value. The need for leeks continues to increase as the population continues to increase. The conditions for the growth of leeks are nutritional requirements, being at an altitude of 230-1500 m above sea level, rainfall ranging from 15-200 mm/year, and having a daily temperature of 18-250C and suitable soil types are andosols, latosol, and regosol. Shallots will grow maximally if they are protected from weeds, pests, and diseases. The decrease in leeks is caused by the abundance of Imperata cylindrica L. , the magnitude of the decrease is 40-50%, so Imperata cylindrica L. control is necessary. Imperata cylindrica L.  control is usually done by farmers using chemical herbicides which over time will cause plants to become resistant to chemical herbicides and will cause the soil to decrease infertility, it is necessary to control weeds using weeds themselves because Imperata cylindrica L.  have allelopathic chemical compounds that can inhibit plant growth. the use of organic herbicides can use Imperata cylindrica L.  and Ageratum conyzoides L. because these two plants have active compounds in the form of phenols, terpanoids, flavonoids, and also tannins. This study used variations in concentrations of 10%, 20%, 30%, 40%, positive control, and negative control and the results obtained that there was no right concentration to control Imperata cylindrica L. Kata kunci: Bandotan, Bawang daun, Bioherbisida, Ilalang